2013
DOI: 10.1111/ceo.12098
|View full text |Cite
|
Sign up to set email alerts
|

Manchester iStent study: early results from a prospective UK case series

Abstract: The iStent proved to be a safe and effective treatment for patients with open-angle glaucoma over our 6-month follow up period. Insertion resulted in a significant decrease in intraocular pressure as well as the number of topical antiglaucoma medications required for adequate intraocular pressure control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…This is consistent with previous studies that have suggested that the IOPlowering effect after iStent/CEIOL surgery was achieved by 3 months and persisted through at least 6 to 12 months postoperatively. 2,12 We also found that patients who were receiving 3 or more glaucoma medications preoperatively were more likely than those receiving only 1 medication at baseline to achieve postoperative glaucoma medication reduction. Several studies have reported that patients receiving more glaucoma medications or more complex medication regimens may have greater difficulty with medication adherence.…”
Section: Discussionmentioning
confidence: 63%
“…This is consistent with previous studies that have suggested that the IOPlowering effect after iStent/CEIOL surgery was achieved by 3 months and persisted through at least 6 to 12 months postoperatively. 2,12 We also found that patients who were receiving 3 or more glaucoma medications preoperatively were more likely than those receiving only 1 medication at baseline to achieve postoperative glaucoma medication reduction. Several studies have reported that patients receiving more glaucoma medications or more complex medication regimens may have greater difficulty with medication adherence.…”
Section: Discussionmentioning
confidence: 63%
“…Stent or tube malposition or obstruction has been reported in 4-18.0% of cases in iStents, 2,3,17 8.8% in Cypass, 12 and 3.0% in Baerveldt tube. 18 Only one patient (2.6%) developed hyphaema in our cohort, compared to 2.3% in iStent, 19 2.0% in Baerveldt tube, 18 and 6-24.6% in the trabeculectomy studies. 7,16,18 As the IOP tends to be the lowest immediately post surgery, hyphaema can occur due to the lack of an IOP tamponade.…”
Section: Discussionmentioning
confidence: 54%
“…iStents and Trabectome surgeries are often combined with cataract extraction to improve vision and lower pressure. Complications from these new procedures are significantly lower than conventional filtration surgeries; hyphema appears to be the most common risk attached to stent devices and Trabectome within the initial postoperative period with no long-term consequence 6 8 9. Patients can now benefit from an effective, minimally invasive glaucoma procedure with fast visual improvement and the low complication rate that we have all enjoyed for years with small incision phacoemulsification.…”
mentioning
confidence: 99%